APLIKASI TEKNIK QUALITY FUNCTION DEPLOYMENT DAN LEAN MANUFACTURING UNTUK MINIMASI WASTE - Rahmawan, Arief; Sugiono, Sugiono (JEMIS (Journal of Engineering & Management in Industrial System), 2014)
The aim of the paper is to reduce wastes in manufacturing process by integrating QFD and lean concepts manufacturing. Optimize the amount of waste can be considered as the voice of consumers e.g. how the management manufacturing eliminated the defect of the product. Some companies have implemented both the integration but not fully eliminate waste entirely. Hence, the modification of QFD & lean concept integration is still open chance to get better in waste (defect) elimination. The study is started with a preliminary survey and assesses the theory to define both methods. Pareto diagram is employed to determine the level of interest which has priority waste and further analyzed with QFD achieved. The result shows that a unique standard operating procedure (SOP) is very important for every department.